Mathematics
huleaflorin2f
5

Is the expression -12x-18 equivalent to the expression -6x-9-3(3-2x)

+0
(2) Answers
Tess13

-12x-18 and -6x-9-3(3-2x) First, distribute the -3 into the parentheses. The second expression will turn out as such: -6x-9-9-6x. From here, you need to combine like terms (variables and numbers). -12x-18. So, yes, these two expressions are equal.

QueenieRoesler

-12x-18=-6x-9-3(3-2x) -12x-18=-6x-9-9+6x -12x-18=-6x+6x-9-9 -12x-18=-18 -12x-18=-18 +18=+18 -12x=0 X=0

Add answer